Activity and Stability of the Alcohol Biosensor Using Acetobacter aceti Biofilm on Screen-Printed Carbon Electrode - Dyah Iswantini; Fitriani Indahsari; Akhiruddin Maddu; Novik Nurhidayat; Henny Purwaningsih; Sri Sugiarti (HAYATI Journal of Biosciences, 2020)
Most of the alcohol analytical methods are robust and instrumentally expensive. An alternative of ethanol biosensor based on selected biofilm forming Acetobacter aceti bacteria producing alcohol oxidase was constructed on a screen-printed carbon electrode. The enzyme specifically oxidizes the ethanol and generate electrical current that then electrochemically detected and measured by cyclic voltammetry method. A scanning electron microscopic analysis indicated that the biofilm was formed firmly in the electrode. This constructed biosensor reached its optimum at biofilm formed by bacteria of 1.33 × 1010 cells/ml, temperature of 27°C, and pH 7. The enzyme kinetic had KM and Vmax AOX values of 3.5 mm and 125 μA respectively. The biosensor had detection and quantization limit of 0.003 and 0.009%, respectively, and a sensitivity of 57.29 μA (%)-1. A linearity and relative deviation value were revealed at 0.993 and 1.95% respectively. The biosensor was relatively specific and had no interferences with methanol, sodium chloride and citric acid as the common interferences of ethanol compounds. Furthermore, the biosensor had been stably for at least 55 days. Therefore, this constructed biosensor should be developed into a prototype for a practical effective analysis.